Secular and its Cognate Terms - Khan, Muhammad Arif; Shahid, Shahid Hussain (Annals of Human and Social Sciences, 2022)
The objectives of the research include the investigation and analysis of the term secular, secularity, secularization and secularism. This is done in the backdrop of ever changing and challenging socio political global existential structure which encompasses and governs both public and private lives of individuals and societies. Although Western in origin these concepts are not unfamiliar in nonwestern worlds and have diverse and conflicting meanings. Secular pertains to this worldliness devoid of religion. Secularity is a condition of being secular which exists in thoughts, ideologies and practices that belong not to religion. Secularization is a historical, anthropological, and social condition which has remained engaged in removing religious influences from lifestyles of people. Secularism is assumed to be a belief system which gives no room to religion in human existential set up. The study explanatory, explorative and. This research finds that the secular and its cognate terms are now an undeniable reality and condition beyond Western borders. It recommends that the secular in any of its forms needs to be seen as an ideology opposite to religion.